2014
DOI: 10.1136/annrheumdis-2013-203695
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of certolizumab pegol in combination with methotrexate in the treatment of rheumatoid arthritis: 5-year results from the RAPID 1 trial and open-label extension

Abstract: ObjectivesTo examine the safety and efficacy of 5-year administration of certolizumab pegol (CZP)+methotrexate (MTX) in patients with active rheumatoid arthritis (RA).MethodsEligible patients from the Rheumatoid Arthritis Prevention of Structural Damage (RAPID)1 randomised controlled trial (RCT) were treated in open-label extension (OLE) with CZP 400 mg every other week (Q2W), reduced to 200 mg Q2W after ≥6 months, +MTX. Combined safety data from RCT and OLE are presented from initiation of CZP treatment to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
31
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 24 publications
11
31
0
3
Order By: Relevance
“…The long-term safety and efficacy of CZP reported here appears comparable to studies with other anti-TNFs [19-21, 24, 26], however, comparisons are limited due to differences in study design. These results not only confirm previously reported short-term data from the RAPID 2 RCT [2], they additionally support and expand the results from the RAPID 1 clinical trial and OLE [17]. Improvements reported in minimally clinically important difference (MCID) for health-assessment questionnaire-disability index (HAQ-DI), patient's assessment of arthritic pain, patient's global assessment of disease activity (PtGA), short form-36 physical component summary (SF-36 PCS) and fatigue in certolizumab pegol (CZP) intention-to-treat (a) and CZP completers (b).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The long-term safety and efficacy of CZP reported here appears comparable to studies with other anti-TNFs [19-21, 24, 26], however, comparisons are limited due to differences in study design. These results not only confirm previously reported short-term data from the RAPID 2 RCT [2], they additionally support and expand the results from the RAPID 1 clinical trial and OLE [17]. Improvements reported in minimally clinically important difference (MCID) for health-assessment questionnaire-disability index (HAQ-DI), patient's assessment of arthritic pain, patient's global assessment of disease activity (PtGA), short form-36 physical component summary (SF-36 PCS) and fatigue in certolizumab pegol (CZP) intention-to-treat (a) and CZP completers (b).…”
Section: Discussionsupporting
confidence: 81%
“…However, it should be noted that patient retention in clinical trials is often better than in real-world clinical practice. Clinical (ACR20/50/70, DAS28(ESR)) and patient-reported (HAQ-DI, PtGA, pain, fatigue, SF-36 PCS) improvements in RA signs, symptoms, and physical function observed over the 24-week RAPID 2 RCT were maintained for up to approximately 4.5 years in both the CZP ITT and week-24 CZP completer populations, consistent with sustained improvements observed in the RAPID 1 study [17]. Efficacy was also maintained in the dose-reduction population, demonstrating that CZP 200 mg Q2W + MTX was just as efficacious as CZP 400 mg Q2W + MTX during the maintenance phase.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…[37][38][39] Studies have shown certolizumab pegol to be as effective as the other anti-TNF agents. Particularly in pregnancy, certolizumab passes through placenta in smaller amounts than other TNF inhibitors and its level in umbilical cord blood is low.…”
Section: Discussionmentioning
confidence: 99%